Heritable changes in regional cortical thickness with age. - Chouinard-Decorte, Francois; McKay, D Reese; Reid, Andrew; Khundrakpam, Budhachandra; Zhao, Lu; Karama, Sherif; Rioux, Pierre; Sprooten, Emma; Knowles, Emma; Kent Jr, Jack W; Curran, Joanne E; Göring, Harald H H; et al. (Brain Imaging & Behavior, 2014)
It is now well established that regional indices of brain structure such as cortical thickness, surface area or grey matter volume exhibit spatially variable patterns of heritability. However, a recent study found these patterns to change with age during development, a result supported by gene expression studies. Changes in heritability have not been investigated in adulthood so far and could have important implications in the study of heritability and genetic correlations in the brain as well as in the discovery of specific genes explaining them. Herein, we tested for genotype by age (G ×A) interactions, an extension of genotype by environment interactions, through adulthood and healthy aging in 902 subjects from the Genetics of Brain Structure (GOBS) study. A "jackknife" based method for the analysis of stable cortical thickness clusters (JASC) and scale selection is also introduced. Although additive genetic variance remained constant throughout adulthood, we found evidence for incomplete pleiotropy across age in the cortical thickness of paralimbic and parieto-temporal areas. This suggests that different genetic factors account for cortical thickness heritability at different ages in these regions.